Representing Women's Empowerment Through Key Visual Elements In Wicked (2024): A Barthesian Semiotic Analysis - Siti Nursaida (CV. SINAR HOWUHOWU, 2026)
Films do more than entertain; they also shape public understanding of social issues, including gender equality and women's empowerment. As a contemporary fantasy musical, Wicked (2024) offers a compelling portrayal of two female protagonists whose contrasting experiences of discrimination, identity, and friendship gradually evolve into a shared journey of empowerment. This study aims to explore how women's empowerment is represented through the film's key visual elements and narrative development. Using a qualitative descriptive design with a semiotic approach, the study examines selected scenes, dialogues, songs, and cinematic techniques through the concepts of denotation, connotation, and myth. The findings indicate that women's empowerment is portrayed not as an immediate achievement but as a continuous process shaped by marginalization, self-acceptance, resistance to social prejudice, and mutual support. Cinematic elements, including costume, lighting, camera angles, movement, and visual symbolism, reinforce the transformation of the protagonists from social exclusion to confidence and agency. The study concludes that Wicked reconstructs the meaning of women's empowerment by presenting resilience, authentic identity, and female solidarity as forces that challenge conventional expectations of femininity and authority. These findings demonstrate how semiotic analysis can uncover the ideological meanings embedded in contemporary cinematic representations of women while contributing to broader discussions in film, media, and cultural studies.